Instrumente pentru protecția internațională a drepturilor femeilor - Mihaela-Corina Bucur (Drepturile Omului)
Despite the evolution of society, discrimination against women continues to manifest itself by limiting their political, economic, social, cultural, and civil rights and freedoms, thereby violating the fundamental human rights principle of equality between women and men. Furthermore, serious forms of violence still persist such as: domestic violence, sexual harassment, rape, forced marriage, so-called ”honor” crimes, femicide, feminicide and genital mutilation, women being much more exposed to gender-based violence, with domestic violence particularly affecting them in a disproportionate manner. The promotion and protection of women’s rights have been the subject of public international law regulations since the 20th century. The process of affirming women’s rights at the international level has been long and arduous, beginning with the declaration of principles by various movements in different countries, and evolving into the development of international regulations under the auspices of the United Nations. Measures to promote equal opportunities between women and men have begun to yield initial results; however, there is a pressing need to refine the system for protecting victims of domestic violence, particularly through increased public awareness and the provision of necessary resources to effectively carry out protection activities for individuals who have suffered abuse. The controversial positioning of women’s rights within the broader framework of human rights is also reflected in the evolution of European and international documents and agreements through which women’s rights have been established, and violations of these rights have been condemned globally by international bodies and organizations, including the United Nations.